Strategic approaches in disaster management: Analyzing the roles of public health professionals from emergency response to post-disaster recovery - Ramada, Andro (Journal of Evidence-based Nursing and Public Health, 2024)
Disaster management presents a global challenge requiring the coordinated efforts of various sectors, especially public health professionals. The COVID-19 pandemic, declared by WHO in March 2020, marked a paradigm shift in disaster management and public health responses. This study examines the role of public health professionals during different disaster management phases, with a focus on Indonesia and global examples. Findings from Siti Marlina et al. (2022) and O. Olu (2017) highlight the critical role of community health centers and resilient health systems. The research also explores the Lombok earthquake response (Xu et al., 2018; Skinner, 2018; Kunugita et al., 2018; Brun & Pakenham-Walsh, 2018) and the broader implications of disaster management trends in Spain (Arcos González et al., 2023) and nuclear event concerns (Dallas, 2022). The study underscores the importance of mental health support (Peppou et al., 2021; Raesi et al., 2020) and offers recommendations for improving disaster management, including enhancing training, integrating public health into planning, and leveraging technology.